2007
DOI: 10.1007/s10654-006-9092-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life as a predictor of mortality among community-dwelling older persons

Abstract: Health-related quality of life (HRQOL) measures predict cause-specific mortality, but few studies have explored whether generic self-reported HRQOL measures are independently associated with mortality in community-dwelling older persons. We postulated that a general measure of HRQOL, the short form 36-item questionnaire (SF-36), would be independently predictive of mortality among community-dwelling older persons. To evaluate this hypothesis, we followed a fixed cohort of 4,424 community-dwelling older persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 31 publications
5
87
0
6
Order By: Relevance
“…As the self-assessment of health is significantly associated with clinical conditions and mortality 4,50 , beyond the results of objective measures 5,51 , and considers different health dimensions, studies on the association between self-assessed health and sleep duration can provide important information for health management in the elderly. The present study is one of the first to describe this association and broaden knowledge on the relationship between long sleep duration patterns and health outcomes, an area which merits further research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the self-assessment of health is significantly associated with clinical conditions and mortality 4,50 , beyond the results of objective measures 5,51 , and considers different health dimensions, studies on the association between self-assessed health and sleep duration can provide important information for health management in the elderly. The present study is one of the first to describe this association and broaden knowledge on the relationship between long sleep duration patterns and health outcomes, an area which merits further research.…”
Section: Resultsmentioning
confidence: 99%
“…This instrument assesses different dimensions of health in individuals or populations such as the physical, emotional and social aspects of quality of life, bodily pain, mental health, vitality and general health 1 . A number of studies report a strong correlation between the health dimensions addressed by the SF-36 and the presence of health conditions and clinical symptoms 2,3 and also suggest that self-assessment may serve to predict mortality 4 . The measurement of health status dimensions provides useful indicators of health conditions and wellbeing that may complement evaluations of illness and mortality indicators 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in nondiabetic populations have also found that factors like worse health-related quality of life (HRQOL) are associated with higher mortality (2)(3)(4). If this holds true for patients with type 2 diabetes, clinicians might have to give more attention to HRQOL and perhaps assess HRQOL routinely in these patients.…”
mentioning
confidence: 99%
“…The MOS Short-form 36-item (SF-36) Health Survey has become a popular HRQOL measure worldwide since its first publication in 1992. Studies have shown that SF-36 can predict the utilization of primary care services [89], and low HRQOL in community-dwelling elderly had higher mortality rates [90]. Patients with gouts were found to have poorer HRQOL (lower functional limitation scores of the SF-36 Health Survey) and higher rates of inpatient utilization and mortality among all US veterans [91].…”
Section: Hrqol In Measuring Effectiveness Of Primary Carementioning
confidence: 99%